Outsourcing and occupational health and safety: a comparative study of factory-based and outworkers in the Australian TCF industry - Mayhew, Claire; Quinlan, Michael (University of New South Wales, 1998)
This new monograph examines OHS in the Textile, Clothing and Footwear (TCF) industry. The study involved an assessment of the incidence and patterns of work-related injury and illness amongst 100 factory-based TCF workers, which was compared with the injury patterns identified amongst 100 outworkers. It was found that overuse injury was the most common condition in both groups, although the factory-based workers had a far lower incidence than did outworkers. However bonus and piecework payment systems significantly increased the probability of an overuse injury amongst factory-based TCF workers. Factory-based TCF workers were heavily reliant on their supervisors and union officials for any OHS preventive information. Outworkers had no readily available access to OHS supports, and were vulnerable to the "middlemen" who provided them with work.